Guru Profesional dalam Perspektif Al-Qur'an: Karakteristik, Peran, dan Tanggung Jawab dalam Pendidikan Islam - Muhammad Fadhil; Halimatun Sa’diah; Elsa Martineli; Sri Bulan (Departement of Mathematics Education, 2024)
Education plays a crucial role in shaping a knowledgeable and morally upright generation, with teachers holding a key position. This study aims to analyze the characteristics of a professional teacher according to the perspective of the Qur'an. Using a qualitative approach with a library research method, this study analyzes relevant Qur'anic verses on education and the role of teachers, along with supporting literature such as tafsir, hadith, and books on Islamic education. The results reveal that the Qur'an emphasizes the role of teachers not only as knowledge transmitters but also as moral and spiritual guides. The concept of a professional teacher in the Qur'an encompasses dimensions of knowledge, morality, and social responsibility. This research contributes significantly to the development of Islamic education and provides guidance for educators to fulfill their roles with integrity and responsibility in line with Islamic teachings.